Danish general practitioners’ management of patients with COPD: a nationwide survey - Katrine Rutkær Molin; Jens Søndergaard; Peter Lange; Ingrid Egerod; Henning Langberg; Jesper Lykkegaard (Scandinavian Journal of Primary Health Care, 2020)
Background In Denmark, general practitioners (GPs) have the main responsibility for chronic obstructive pulmonary disease (COPD) management. Internationally, COPD appears to be significantly under-treated, which could be explained by ‘therapeutic nihilism’ or lack of knowledge. Aim To investigate: (1) To what extent COPD management provided by GPs includes the core elements of pharmacological treatment, smoking cessation and physical activity, and (2) To what extent GPs need educational support and consulting with a specialist in pulmonary medicine. Design A national cross-sectional web-based survey conducted in April–June 2019. The survey included items on COPD management and educational support needs. Setting Danish general practice. Subjects A population of approximately 3400 GPs (all GPs in Denmark). Results We received response from 470 GPs (14% response rate). Overall, the respondents reported that they offered COPD management including all relevant treatment elements. Smoking cessation was supported in 58% and physical activity was supported in 23% of the respondents. Future consultations on smoking cessation were planned by 35% and physical activity by 15% respondents. GPs responded to ‘needing educational support in COPD management’ to a ‘high degree’ in 8% and to ‘some degree’ in 43%. Conclusion The survey suggested that COPD maintenance support provided by GPs seemed to be inadequate regarding smoking cessation and physical activity. Moreover, some GPs expressed a need for educational support in COPD management. More research is needed to understand the potential barriers to evidence-based delivery of COPD-management.Key points In Denmark, general practitioners (GPs) have the main responsibility for the management of chronic obstructive pulmonary disease (COPD). The present study shows that non-pharmacological interventions such as supporting smoking cessation and particularly promoting physical activity received less attention than pharmacological treatment. The study suggests a need for educational support of the GPs in COPD management.